2010
DOI: 10.1007/s10530-010-9865-x
|View full text |Cite
|
Sign up to set email alerts
|

Cuscuta australis restrains three exotic invasive plants and benefits native species

Abstract: In this study we conducted field investigations to examine the effects of native Cuscuta australis on three exotic invasive plants (i.e. Ipomoea cairica, Mikania micrantha, and Wedelia trilobata) and on the invaded native communities. The results showed that C. australis produced high infection rates on the exotic invasive hosts but low ones on the native species. Furthermore, the results showed that C. australis exhibited vigorous growth and high reproduction when it grew on M. micrantha and W. trilobata, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 44 publications
2
40
0
2
Order By: Relevance
“…The extracts may contain a lot of water, as can be seen in the non-deleterious effects of the extracts of fresh and dried plant materials of dodder on germination of radish and lettuce, registering almost100% germination. Seed germination of radish was inhibited by the ethanol extracts of dodder in excess of 5000ppm, while the growth of radish and lettuce seedlings as test plants were inhibited by dodder's ethanol extracts in excess of 200ppm.In fact, several previous studies have been carried out had proved that certain types of weeds can be slowed or inhibited the growth by using aqueous extracts allelopathic plant samples (Khanh et al2008;Macías 2007;Omezzine et al 2011;Yu et al 2011). Khanh (2008) suggested that allelochemicals from parasitic plants, including Cuscuta spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts may contain a lot of water, as can be seen in the non-deleterious effects of the extracts of fresh and dried plant materials of dodder on germination of radish and lettuce, registering almost100% germination. Seed germination of radish was inhibited by the ethanol extracts of dodder in excess of 5000ppm, while the growth of radish and lettuce seedlings as test plants were inhibited by dodder's ethanol extracts in excess of 200ppm.In fact, several previous studies have been carried out had proved that certain types of weeds can be slowed or inhibited the growth by using aqueous extracts allelopathic plant samples (Khanh et al2008;Macías 2007;Omezzine et al 2011;Yu et al 2011). Khanh (2008) suggested that allelochemicals from parasitic plants, including Cuscuta spp.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this study also proves that there are allelochemicals in Cuscuta campestris and many Cuscuta spp. inhibited the growth and the germination of seeds, including weeds that can influence plant population density (Yu et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Biological control of invasive plants uses parasitic plants to infect and control the invasive plants161718. This may affect the ecological interactions between invasive species and other biotic and abiotic factors at different trophic levels in invaded communities, as well as alter soil microbial communities, nutrient cycling and greenhouse gas emission.…”
mentioning
confidence: 99%
“…The presence of invasive plant species such as S. trilobata in the islands terrestrial ecosystem poses a major threat to the biodiversity of a given community and ecosystem functions [12,13]. S. trilobata was found to prevent regeneration of co-occurring species and damage riverbanks and wastelands [14]. This could have been attributed to the allelopathic effect of S. trilobata leachates and residues that caused substantial reduction in germination and growth rate of tested crop and native plants in China [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, Cuscuta australis R. Brown, a holoparasitic rootless annual plant found to decrease the growth and nutrient content of S. trilobata in a field study in China had been recommended as a potential biological control for the invasive species [14]. Cuscuta species have been observed on S. trilobata in some sites in Viti Levu Fiji (personal observation).…”
Section: Introductionmentioning
confidence: 99%